1993
DOI: 10.1073/pnas.90.14.6721
|View full text |Cite
|
Sign up to set email alerts
|

The serum response element can mediate induction of c-fos by growth hormone.

Abstract: The c-fos protooncogene is transcriptionaily activated by a wide variety of agents including serum, growth factors, and phorbol esters. This induction is rapid and transient and is mediated through a number of identified promoter elements. Growth hormone (GH) is also known to induce transcription of c-fos in a variety of cell tpes including NIH 3T3 fibroblasts and 3T3-F442A preadipocytes. To identify DNA sequences in the c-fos gene regulated by GH, this study sought to determine whether induction of c-fos by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…GH also rapidly activates other genes in vivo through additional signal transduction pathways. As seen in this report, the early-response gene, c-fos, is induced with kinetics similar to those of IGF-I, but as expected is unmodified by dominant-negative or constitutively active Stat5b, because previous studies have demonstrated that c-fos gene transcription is stimulated by GH through pathways involving Stats 1 and 3, and the Erk-activated Elk-1 transcription factor (28,32,33).…”
Section: Assessing Signal Transduction Pathways Regulated By Gh In Hysupporting
confidence: 78%
“…GH also rapidly activates other genes in vivo through additional signal transduction pathways. As seen in this report, the early-response gene, c-fos, is induced with kinetics similar to those of IGF-I, but as expected is unmodified by dominant-negative or constitutively active Stat5b, because previous studies have demonstrated that c-fos gene transcription is stimulated by GH through pathways involving Stats 1 and 3, and the Erk-activated Elk-1 transcription factor (28,32,33).…”
Section: Assessing Signal Transduction Pathways Regulated By Gh In Hysupporting
confidence: 78%
“…In 3T3-F442A fibroblasts, CHO and COS cells expressing cloned rat liver GH receptor, and livers from hypophysectomized rats, GH was found to stimulate the binding of Stats 1, 3 and 5 [15][16][17][18][19][20]. No phosphorylation of Stat2 was observed [21]. Consistent with Stats 1, 3 and 5 serving as signalling molecules for GH, GH was also shown to promote the binding of Stats 1, 3 and 5 to DNA.…”
mentioning
confidence: 99%
“…Activation of gene transcription by GH also can be mediated through other types of cis element. For example, GH rapidly activates transcription of the early response gene c-fos through a sequence known as the serum response element (SRE), and of the serine protease inhibitor (Spi) 2·1 gene through purine-rich sequences (Le Cam et al 1994, Meyer et al 1993. The trans acting factors that bind to these cis elements are probably unrelated to the STAT proteins.…”
Section: Discussionmentioning
confidence: 99%